Β‐Blocker withdrawal is preferable for accurate interpretation of the aldosterone–renin ratio in chronically treated hypertension. (22nd September 2015) - Browne, Gerard A.; Griffin, Tomás P.; O'Shea, Paula M.; Dennedy, Michael Conall
Summary: Objectives: To evaluate the effects of β‐adrenoreceptor antagonists (β‐blockers) on the aldosterone–renin ratio (ARR) in the context of antihypertensive polypharmacy in chronic hypertension. To determine the optimal duration of β‐blocker withdrawal required to normalize the ARR. Design: A prospective, longitudinal study design was employed investigating two groups whom either remained on or withdrew from β‐blocker therapy. Methods: Hypertensive individuals taking β‐blockers and a combination of thiazide diuretics, α1‐blockers, calcium channel antagonists and angiotensin‐converting enzyme inhibitor/angiotensin receptor blocker were recruited and followed over 10–12 weeks. β‐Blockers were withdrawn at the first visit. Blood pressure (BP) was measured at each visit and blood drawn serially for measurement of plasma renin activity (PRA), direct renin concentration (DRC) and aldosterone. BP was optimized by maximizing non‐renin‐suppressing antihypertensives. Main outcomes were ARR, DRC, PRA and aldosterone. Plasma renin activity was calculated from angiotensin I measured using radioimmunoassay (RIA), DRC was measured using chemiluminescent immunoassay assay, and aldosterone was measured using both RIA and Chemilluminescence Assay (CIL). Results: False‐positive ARR for primary aldosteronism (PA) occurred in 31% of patients taking β‐blockers. ARR returned to normal following β‐blocker withdrawal resulting from an increase in the DRC and PRA without affecting aldosterone. The optimum time for β‐blocker withdrawal was 2 weeks when using DRC and 3 weeks for PRA. β‐Blocker withdrawal did not adversely affect blood pressure. Conclusion: Raised ARR consequent to β‐blocker therapy causes false‐positive screening for PA. Where β‐blockers can be safely withdrawn, this effect is reversed within 2–3 weeks depending on whether DRC or PRA is used to calculate ARR.